Profil Pasien Kanker Kolorektal di RSUD Dr. H. Abdoel Moeloek Periode Januari 2022-Desember 2024 - Muhammad Satria; Marcella Andinatania (CV. Jasa Sukses Abadi, 2026)
Colorectal cancer is a malignancy of the colon or rectum and is one of the leading causes of cancer-related morbidity and mortality worldwide. It ranks as the third most commonly diagnosed cancer, with more than 1.9 million new cases annually, and as the second leading cause of cancer-related death, accounting for approximately 935,000 deaths each year. In Indonesia, the incidence of colorectal cancer continues to rise, reaching 12.4 cases per 100,000 population. The majority of cases are diagnosed at an advanced stage and are often accompanied by metastatic disease. This trend is primarily attributed to inadequate early detection and screening programs, resulting in limited therapeutic options and poorer prognosis. This study aims to describe the profile of colorectal cancer patients who underwent evaluation and management at RSUD Dr. H. Abdoel Moeloek from January 2022 to December 2024. Methods: This study employed a retrospective descriptive design involving 100 colorectal cancer patients at Dr. H. Abdoel Moeloek General Hospital from January 2022 to December 2024 who met the inclusion criteria. Variables assessed included sex, age, tumor location, and histopathological findings. Data were presented in frequency and percentage distributions. Results: A total of 56 males (56%) and 44 females (44%) were included in this study, with the majority aged 45–50 years (39%). The rectum was the most common tumor location (61%), and adenocarcinoma was the predominant histopathological type (82%).